The structural and dynamic responses of Stange Ice Shelf to recent environmental change. Issue 6 (13th November 2014) - Holt, T.O.; Glasser, N.F.; Fricker, H.A.; Padman, L.; Luckman, A.; King, O.; Quincey, D.J.; Siegfried, M.R.
Abstract: Stange Ice Shelf is the most south-westerly ice shelf on the Antarctic Peninsula, a region where positive trends in atmospheric and oceanic temperatures have been recently documented. In this paper, we use a range of remotely sensed datasets to evaluate the structural and dynamic responses of Stange Ice Shelf to these environmental changes. Ice shelf extent and surface structures were examined at regular intervals from optical and radar satellite imagery between 1973 and 2011. Surface speeds were estimated in 1989, 2004 and 2010 by tracking surface features in successive satellite images. Surface elevation change was estimated using radar altimetry data acquired between 1992 and 2008 by the European Remote Sensing Satellite (ERS) -1, -2 and Envisat. The mean number of surface melt days was estimated using the intensity of backscatter from Envisat's Advanced Synthetic Aperture Radar instrument between 2006 and 2012. These results show significant shear fracturing in the southern portion of the ice shelf linked to enhanced flow speed as a consequence of measured thinning. However, we conclude that, despite the observed changes, Stange Ice Shelf is currently stable.